Analysis of The Influence of RGEC, BI Rate, and Inflation on Stock Return - Venni Avionita; Afifa Nurhanifah; Fitri Fitri; Neneng Anis Nurhasanah (Accounthink : Journal of Accounting and Finance, 2023)
The purpose of this research is to analyze the influence of the soundness level of the bank which consists of four groups, namely Risk Profile, Good Corporate Governance, Earnings, and Capital or which can be abbreviated as RGEC as well as external factors, namely BI Rate and Inflation on Stock Returns in 23 registered banking companies on the Indonesia Stock Exchange (IDX) in 2016 – 2020. Based on statistical tests, the independent variables namely RGEC, BI Rate, and Inflation are together able to explain the variation of Stock Return of 86.0065% and can be interpreted as having a strong relationship, so that the remaining is 13.9935 % explained that stock returns can be influenced by other factors that are not contained in this model.